USEOFSODIUMBEMIPARININOBSTETRICPRACTICE. A CLINICAL CASE - D. Kh. Khizroeva; D. V. Mitryuk (IRBIS LLC, 2017)
The report presents a case of pregnancy management in a woman with a history of obstetric problems and neurosensory hearing loss. After thorough hemostasis tests, the presence of antiphospholipid antibodies in the blood was detected. Given a high risk of thrombophilia in this situation, the patient was treated with antithrombotic therapy - low molecular weight heparin (sodium bemiparin).